2001
DOI: 10.3346/jkms.2001.16.4.439
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal and Nonparenchymal Cellular Responses in Human Hepatic Regeneration

Abstract: To characterize cellular responses during hepatic regeneration, we examined 13 explant livers and 5 liver allografts by immunohistochemistry for cytokeratin 7, HepPar1, CD68, alpha-smooth muscle actin (alpha-SMA) and proliferating cell nuclear antigen as well as reticulin and Masson-trichrome staining. Within a week after liver damage, elongated CD68-positive cells were detected along the border of necrotic area. The number of alpha-SMA-positive cells was slightly increased along the sinusoids. Ductular prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This relation has, however, not substantially been shown in dogs. Moreover, studies focusing on the relationship between the LPC and the HSC/MF are scarce, as are studies investigating diseases with different histopathological conditions (12,16,45,63,67,68). Finally, the subtype of HSC/MF involved in different types of disease has not been specified.…”
mentioning
confidence: 99%
“…This relation has, however, not substantially been shown in dogs. Moreover, studies focusing on the relationship between the LPC and the HSC/MF are scarce, as are studies investigating diseases with different histopathological conditions (12,16,45,63,67,68). Finally, the subtype of HSC/MF involved in different types of disease has not been specified.…”
mentioning
confidence: 99%
“…Since most patients with fulminant hepatic failure have fatal clinical courses, liver transplantation became the ultimate therapeutic modality for MHN. Thus, the explanted liver of MHN has been used to observe sequential histopathological characteristics of hepatic regeneration 22 as well as to detect the presence of hepatic stem cells 23…”
Section: Introductionmentioning
confidence: 99%
“…21 Since most patients with fulminant hepatic failure have fatal clinical courses, liver transplantation became the ultimate therapeutic modality for MHN. Thus, the explanted liver of MHN has been used to observe sequential histopathological characteristics of hepatic regeneration 22 as well as to detect the presence of hepatic stem cells. 23 In the present study, we observed that potential hepatic stem cells expressing c-kit and CD133 appear primarily along the portoparenchymal interface and rarely in the parenchyma at the early stage of hepatic regeneration, and that their numbers increase during the regeneration process.…”
Section: Introductionmentioning
confidence: 99%